Critical Dietary Factors in Cancer Chemoprevention - Ullah, Mohammad Fahad; Ahmad, Aamir; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book focuses on the prophylactic potential of diet-derived factors in primary prevention of cancer. It is written by a group of highly reputed experts in the area of dietary agents and cancer chemoprevention. The translational potential of dietary factors from epidemiological, laboratory and clinical studies as prevention strategy in normal and risk populations is highlighted. The work presents options of routine inclusion of specific dietary regimens for prevention as well as therapeutic strategy for better management through adjuvant interventions in cancer treatment.
i. Foreword -- ii. Preface -- Commentary  (Translational insights into the role of dietary agents in cancer chemoprevention: Lets walk the talk)-Expert opinion -- iii. Preliminary chapter titles: -- 1. Modulation of key signaling pathways in cancer cells by dietary factors -- 2. Influence of neuropsychological social stress in cancer progression and neutralization by GABA -- 3. Targeted therapy of prostate cancer with nutraceutical loaded nanoparticles -- 4. Ascorbic acid in cancer chemoprevention: Laboratory and clinical evidences -- 5. Pharmacological potential of black raspberry-derived anthocyanins against colon cancer -- 6. Mechanisms and therapeutic implications of dietary agents against breast cancer -- 7. Novel perspectives of curcumin and its clinical significance against cancer -- 8. Multi-targeted therapy of cancer by resveratrol and its novel analogues -- 9. Dietary inhibitors of histone deacetylase: Implication in cancer therapeutics -- 10. Cancer multi-drug resistance : sensitization by natural products & dietary agents -- iv. Innovative dietary approaches for cancer management -- 1. Fighting cancer with ketogenic diet -- 2. Probiotics in diet as adjunctive therapy to anticancer treatment.
Keywords: Nutrition .; Oncology; Clinical biochemistry; Nutrition; Oncology; Medical Biochemistry